THE ANTI- CANCER SYNERGISTIC EFFECT OF COLCHICINE AND ON CANCER CELLS PROLIFERATION (IN VITRO STUDY) CHOLOROQUINE (World Bulletin of Public Health, 2022)
This study aimed to investigate the possible in vitro cytotoxicity of Colchicine and Chloroquine.
Keywords: study; cytotoxicity; Colchicine